2018
DOI: 10.1177/0954008317752073
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and thermal degradation kinetics of azomethine-based halogen-free flame-retardant polyphosphonates

Abstract: In this study, azomethine polyphosphonates were synthesized by solution polycondensation of phenylphosphonic dichloride with various azomethine diols such as [4-(4-hydroxy phenyl) iminomethyl] phenol, [(4-(4-hydroxy-3-methoxy phenyl) iminomethyl)] phenol and [4-(4-hydroxy-3-ethoxy phenyl) iminomethyl] phenol using triethylamine catalyst at ambient temperature. The structure of the synthesized polymers was confirmed by Fourier transform infrared and 1H-, 13C- and 31P- nuclear magnetic resonance spectroscopic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This reveals that crosslinking ability was reduced by the increase in silica‐silica interaction led to the aggregation of SiO 2 particle. It was reported that poor adhesion of polymer‐filler interaction expected to decrease the elongation properties slowly with aggregation of filler reinforcement …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reveals that crosslinking ability was reduced by the increase in silica‐silica interaction led to the aggregation of SiO 2 particle. It was reported that poor adhesion of polymer‐filler interaction expected to decrease the elongation properties slowly with aggregation of filler reinforcement …”
Section: Resultsmentioning
confidence: 99%
“…This is reflected in decreased thermo mechanical properties of thermosetting polymers. In order to overcome the existing drawbacks in developing bio‐based thermosetting polymers, the crosslinking ability was improved by incorporation of rigid high strength particulate inorganic fillers which could modify the inherent physical and mechanical properties . Recently, some research have been proceeded with nano sized inorganic fillers, which are expensive, to improve the physical and mechanical properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene oxides have been widely studied as SPEs, and polyphosphonates derived from tetraethylene glycol, which have similar cation binding groups, may exhibit similar cation binding abilities. In addition, it may be possible to tune the cation binding abilities of the polyphosphonates derived from tetraethylene glycol by the appropriate choice of R and X groups 14–17 . Further, similar phosphorus‐containing polymers are typically flame‐resistant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it may be possible to tune the cation binding abilities of the polyphosphonates derived from tetraethylene glycol by the appropriate choice of R and X groups. [14][15][16][17] Further, similar phosphorus-containing polymers are typically flame-resistant. Finally, the presence of 31 P nuclei in the polymer backbone should allow 31 P{ 1 H} NMR spectroscopy to be used to probe the cation binding and its effect on the polymer microstructure.…”
Section: Introductionmentioning
confidence: 99%